Technical feasibility of integrating Amazon river prawn culture during the first phase of tambaqui grow-out in stagnant ponds, using nutrient-rich water - Dantas, Daniela P. [UNESP]; Flickinger, Dallas L. [UNESP]; Costa, Gelcirene A. [UNESP]; Batlouni, Sergio R. [UNESP]; Moraes-Valenti, Patricia [UNESP]; Valenti, Wagner C. [UNESP] (Elsevier, 2020)
The aim of this study was to evaluate the feasibility of producing the Amazon river prawn (Macrobrachium amazonicum) with tambaqui (Colossoma macropomum) in integrated multi-trophic aquaculture (IMTA) systems. An experiment was carried out in a completely randomized design with four treatments (types of production systems) and three replicates per treatment (ponds): prawn monoculture (30 prawns. m−2); fish monoculture (3 fish. m−2); IMTA with prawns and fish free-swimming in the same pond (30 prawns. m−2 and 3 fish. m−2); and IMTA with prawns free-swimming and fish in cages placed inside the ponds (30 prawns. m−2 free-swimming and 40 fish. m−3 in net cages). Prawns and tambaqui in the monocultures received commercial pelleted diets, whereas only the tambaqui received the pelleted diet in the integrated cultures. The experiment lasted 5.7 months. Both the prawns and the fish developed well in stagnant ponds while using nutrient-rich water. The mean final body mass, final body length and productivity of the prawns in the monoculture were higher than those of the prawns in the IMTAs. No significant differences were observed for the survival of the prawns and the tambaqui between treatments, and for the mean final mass of the tambaqui between the monoculture and the IMTA systems. Prawn growth and yield were similar whether the tambaqui was reared free-swimming or in cages. Therefore, the prawns and the tambaqui are compatible for IMTA. Yield in IMTA was ∼0.6 t ha−1 prawns, 5 t ha−1 tambaqui in free-swimming and 3 t ha−1 in net-cages. In conclusion, the culture of Amazon river prawn and tambaqui in IMTA is technically feasible in the first grow-out phase of the tambaqui. This system is flexible and permits different management strategies according to the target markets for each species.
Keywords: Bioenvironmental engineering; Freshwater prawn; IMTA; Integrated aquaculture; Sustainability; Tambaqui